2000
DOI: 10.1021/ol000107r
|View full text |Cite
|
Sign up to set email alerts
|

Amidation of Saturated C−H Bonds Catalyzed by Electron-Deficient Ruthenium and Manganese Porphyrins. A Highly Catalytic Nitrogen Atom Transfer Process

Abstract: Amidation of a variety of hydrocarbons with PhI=NTs catalyzed by ruthenium and manganese meso-tetrakis(pentafluorophenyl)porphyrins 1 and 2 afforded N-substituted amides in up to 92% yields with good to excellent substrate conversions. By employing catalyst 2, exceptionally high turnovers (up to 2600) were achieved, and the amidations can be effected by directly using PhI(OAc)(2)/NH(2)R as amidating reagents; in the case of R = COCF(3) a direct amination was realized in up to 90% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(115 citation statements)
references
References 11 publications
0
111
0
4
Order By: Relevance
“…In an important advance, Che has demonstrated that PhI(OAc) 2 and TsNH 2 can replace the capricious TsN=IPh reagent for C-H insertion reactions with manganese and ruthenium porphyrins (Scheme 17.11) [56]. A similar discovery was made contemporaneously by Espino and Du Bois for intramolecular C-H amination of carbamate and sulfamate esters with rhodium(II) catalysts (vide infra) [57].…”
Section: Intermolecular C-h Amination With Other Metalsmentioning
confidence: 87%
“…In an important advance, Che has demonstrated that PhI(OAc) 2 and TsNH 2 can replace the capricious TsN=IPh reagent for C-H insertion reactions with manganese and ruthenium porphyrins (Scheme 17.11) [56]. A similar discovery was made contemporaneously by Espino and Du Bois for intramolecular C-H amination of carbamate and sulfamate esters with rhodium(II) catalysts (vide infra) [57].…”
Section: Intermolecular C-h Amination With Other Metalsmentioning
confidence: 87%
“…Generally, the most broadly used precursors to the transient metal nitrenes have been aryliminoiodinanes, which are decomposed by a suitable metal complex 77 . In the syntheses described here, the aryliminoiodinanes are produced in situ from the corresponding amine, which makes the overall transformations even more attractive 78 nitrenoids 80,81 . By conducting this nitrene insertion with chiral dirhodium catalyst Rh 2 (S-TCPTAD) 4 , enantioselective transformations can be achieved, as illustrated in Fig.…”
Section: C-h Functionalization By Metal Nitrenoidsmentioning
confidence: 99%
“…[186] The problems generally associated with the isolation and purification of nonstabilized iminoiodananes [187] was circumvented by Che and co-workers with the development of an in situ protocol that generated nitrenes from TsNH 2 and PhI(OAc) 2 in the presence of a manganese-porphyrin catalyst. [188] The practicality of C À H aminations employing metal nitrenes was dramatically increased by a report from Espino and Du Bois, who detailed a highly chemo-and stereoselective process whereby oxazolidinones 217 could be prepared from carbamates 216 through an intramolecular CÀH amination (Scheme 91). [189] The reactive species is believed to be a rhodium-nitrene intermediate arising from an iminoiodinane formed in a reaction between the carbamate and a hypervalent iodine reagent.…”
Section: Metal-catalyzed C à H Activationmentioning
confidence: 99%